Integration of the Spline Function and Fuzzy Logic Algorithm in the Management of Clean Water Filling in a Smart Home System - Zaynidinov H.N.; Hodjaeva D.F., (Innovative: International Multidisciplinary Journal of Applied Technology (2995-486X), 2024)
This research paper presents a mathematical model for controlling the level of clean water in the capacity of a smart home system, integrating a PID controller, cubic splines and fuzzy logic algorithms. The water filling control model in the tank contains an equation of water level dynamics, which takes into account the rate of water intake and outflow, and the use of a PID controller adjusts the water supply rate. Cubic splines provide an approximation of the water level, and fuzzy logic algorithms optimize control. The result of the study confirms the high accuracy and adaptability of the proposed approach, which ensures optimal resource management in smart home systems [1,2,3].